Cu-MOF / chitosan / tannic acid composite adsorbent, preparation method thereof and application of Cu-MOF / chitosan / tannic acid composite adsorbent in uranium adsorption

Through the preparation of Cu-MOF/chitosan/tannic acid composite adsorbent, the functional groups on its surface are used to efficiently adsorb uranium ions, which solves the problems of low efficiency and poor stability of uranium adsorbent materials in the prior art, and achieves high efficiency , stable uranium removal and low-cost treatment effects.

CN119236896APending Publication Date: 2025-01-03HENAN UNIV OF URBAN CONSTR
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411485042.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing uranium adsorbent materials have problems such as low efficiency, poor stability, high cost and difficulty in regeneration when treating uranium-containing wastewater, especially the ion exchange resin is prone to saturation, insufficient durability of inorganic adsorbents in water environments, biomaterial adsorption capacity and Low selectivity.

Method used

The preparation method of Cu-MOF/chitosan/tanninic acid composite adsorbent is prepared by reacting tanninic acid, chitosan and Cu-MOF in glutaraldehyde solution, and then shaking and freeze-drying. , the hydroxyl groups, amino groups and sulfur-containing functional groups on its surface are used to efficiently adsorb uranium ions.

Benefits of technology

A 100% uranium removal rate and excellent selectivity are achieved, which improves the efficiency and stability of treating uranium-containing wastewater, and is easy to regenerate, reducing treatment costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236896A_ABST
    Figure CN119236896A_ABST
Patent Text Reader

Abstract

The invention discloses a Cu-MOF / chitosan / tannic acid composite adsorbent and a preparation method and application thereof to uranium adsorption, and relates to the technical field of uranium-containing wastewater treatment.The preparation method comprises the steps that a certain amount of deionized water is added into a proper amount of tannic acid, stirring is conducted till the deionized water is completely dissolved, then a proper amount of chitosan, Cu-MOF and glacial acetic acid are added, stirring continues, then a proper amount of glutaraldehyde solution is added, stirring is conducted continuously, and the Cu-MOF / tannic acid composite adsorbent is obtained. And after oscillation and freeze drying, the Cu-MOF / chitosan / tannic acid composite adsorbent is obtained. The composite adsorbent prepared by the invention shows an extremely high uranium removal rate in uranium-containing wastewater treatment, and the uranium removal rate can reach 100%. Meanwhile, a competitive adsorption experiment shows that the composite adsorbent disclosed by the invention has excellent selectivity on uranium and can preferentially adsorb uranium ions even in a complex water environment, so that the efficiency and selectivity of treating uranium-containing wastewater are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of uranium-containing wastewater treatment, and in particular to a Cu-MOF / chitosan / tannic acid composite adsorbent, a preparation method thereof, and application of the composite adsorbent in adsorbing uranium. Background Art

[0002] With the acceleration of industrialization, the treatment of uranium-containing wastewater has become a global environmental problem. As a radioactive element, the accumulation of uranium in the environment poses a serious threat to human health and the ecosystem. Therefore, the development of efficient uranium adsorption materials to remove uranium from uranium-containing wastewater has become a research hotspot in the fields of environmental science and materials science.

[0003] At present, a variety of materials have been used for the treatment of uranium-containing wastewater, including ion exchange resins, inorganic adsorbents, and biomaterials. Ion exchange resins have been widely studied due to their high adsorption capacity and selectivity, but they have problems such as easy saturation, difficulty in regeneration, and high cost. Inorganic adsorbents such as metal organic frameworks (MOFs) have attracted attention due to their high specific surface area and rich active sites, but their poor stability in aqueous environments limits their durability in practical applications. Biomaterials such as chitosan are considered promising adsorbents due to their biocompatibility and degradability, but their adsorption capacity and selectivity are generally low. Summary of the invention

[0004] One of the purposes of the present invention is to provide a method for preparing a Cu-MOF / chitosan / tannic acid composite adsorbent, so that the prepared adsorbent not only has a high efficiency of uranium adsorption capacity, but also has good selectivity and stability.

[0005] In order to solve the above technical problems, the present invention adopts the following technical scheme: a method for preparing a Cu-MOF / chitosan / tannic acid composite adsorbent, comprising adding a certain amount of deionized water to an appropriate amount of tannic acid, stirring until completely dissolved, then adding an appropriate amount of chitosan, Cu-MOF and glacial acetic acid, continuing to stir, and then adding an appropriate amount of glutaraldehyde solution, shaking, and freeze-drying to obtain a Cu-MOF / chitosan / tannic acid composite adsorbent.

[0006] Preferably, the preparation steps of the Cu-MOF include: taking an appropriate amount of Cu(NO)2·3H2O and dissolving it in ultrapure water, ultrasonically dissolving an appropriate amount of 4-hydroxy-2-mercapto-5-pyrimidinecarboxylic acid and H3BTC, and adding them to the dissolved Cu(NO)2·3H2O solution, stirring at room temperature, reacting at a certain temperature, and then performing solid-liquid centrifugation, and then washing with anhydrous ethanol for multiple times, placing the washed product in anhydrous ethanol for activation, and drying the activated product to obtain the Cu-MOF.

[0007] More preferably, the concentration of the glutaraldehyde solution is 0.1%.

[0008] More preferably, the shaking method is to shake at a frequency of 150 times per minute for 24 hours in an environment of 45°C.

[0009] In addition, the present invention also provides a Cu-MOF / chitosan / tannic acid composite adsorbent, which is prepared by the above-mentioned preparation method. The adsorbent can be used to adsorb uranium metal in uranium-containing wastewater.

[0010] Compared with the prior art, the present invention has the following beneficial effects:

[0011] 1. The composite adsorbent prepared by the present invention exhibits an extremely high uranium removal rate of 100% in the treatment of uranium-containing wastewater. This is mainly due to the synergistic effect of hydroxyl, amino and sulfur-containing functional groups on the surface of the adsorbent, and the ion exchange process between copper ions and uranium dioxide ions. These characteristics jointly promote the efficient adsorption of uranium.

[0012] 2. Competitive adsorption experiments show that the composite adsorbent of the present invention has excellent selectivity for uranium and can preferentially adsorb uranium ions even in a complex water environment, thereby improving the efficiency and selectivity of treating uranium-containing wastewater.

[0013] 3. Since the tannic acid cross-linked chitosan solidifies the Cu-MOF, the composite adsorbent of the present invention exhibits good stability in an aqueous environment and is easy to regenerate, which allows the adsorbent to be recycled and reduces processing costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 Schematic diagram of the effect of solution pH on uranium adsorption by Cu-MOF@CSTA;

[0015] Figure 2 Schematic diagram of the effect of contact time and adsorption kinetics on Cu-MOF@CSTA adsorption of uranium solution;

[0016] Figure 3 The adsorption isotherm of Cu-MOF@CSTA adsorbing uranium solution and the schematic diagram of adsorption thermodynamics;

[0017] Figure 4 is a schematic diagram of the partition coefficient of competing ions;

[0018] Figure 5 Schematic diagram of BET analysis results of Cu-BTC, Cu-BTC-Hc and Cu-MOF@CSTA;

[0019] Figure 6 Schematic diagram of SEM-EDS analysis results of Cu-MOF@CSTA;

[0020] Figure 7 Schematic diagram of SEM characterization results of Cu-BTC, Cu-BTC-Hc and Cu-MOF@CSTA;

[0021] Figure 8 FTIR spectra of Cu-BTC, Cu-BTC-Hc(Cu-MOF), Cu-MOF@CSTA and Cu-MOF@CSTA-U;

[0022] Fig. 9 (a) is a schematic diagram of the Raman analysis structure of Cu-MOF@CSTA and Cu-MOF@CSTA-U, (b) is the XPS spectra of Cu-MOF@CSTA and Cu-MOF@CSTA-U, and (ch) is the XPS spectra of Cu-MOF@CSTA and Cu-MOF@CSTA-U before and after the adsorption of U(VI). DETAILED DESCRIPTION

[0023] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments and drawings. The contents mentioned in the implementation modes are not intended to limit the present invention.

[0024] Preparation of reagents and materials: copper nitrate trihydrate, benzenetricarboxylic acid, 4-hydroxy-2-mercapto-5-pyrimidinecarboxylic acid, anhydrous ethanol, bayberry tannin, chitosan (PubChem CID: 71853, deacetylation degree ≥ 95%, viscosity 100-200 mPa.s), glacial acetic acid, and glutaraldehyde.

[0025] The preparation method of the Cu-MOF / chitosan / tannic acid composite adsorbent comprises the following steps:

[0026] (1) Preparation of Cu-MOF:

[0027] Take 2.4g of Cu(NO)2·3H2O and dissolve it in 35mL of ultrapure water. Then ultrasonically dissolve 0.0628g of 4-hydroxy-2-mercapto-5-pyrimidinecarboxylic acid and 1.15g of H3BTC and add them to the dissolved Cu(NO)2·3H2O solution. Stir at room temperature for 1h and react at 115℃ for 5h. Then perform solid-liquid centrifugation, wash with anhydrous ethanol three times, activate the washed product in anhydrous ethanol for 15h, and dry the activated product at 35℃ for 18h to obtain Cu-MOF.

[0028] (2) Preparation of Cu-MOF / chitosan / tannic acid composite adsorbent:

[0029] Add 60 mL of deionized water to a beaker containing 1.2 g of tannic acid and stir for 2 hours to completely dissolve it. Add 0.3 g of chitosan, 0.3 g of Cu-MOF and 0.6 mL of glacial acetic acid and continue stirring for 2 hours. Then add 1 mL of 0.1% mass concentration glutaraldehyde solution and oscillate at a frequency of 150 times per minute at 45°C for 24 hours. Finally, freeze-dry the product for 48 hours to obtain a Cu-MOF / chitosan / tannic acid composite adsorbent.

[0030] Since the abbreviation of chitosan is CS and the abbreviation of tannic acid is TA, the adsorbent prepared by the above method is abbreviated as "Cu-MOF@CSTA" in this embodiment.

[0031] Adsorption test and results

[0032] The adsorption test was carried out in a 100 mL centrifuge tube. Using the traditional method, 10 mg Cu-MOF@CSTA (dry weight) was added to a centrifuge tube containing 90 mL uranium solution. The initial pH of the solution was adjusted with 0.01 M / L sodium carbonate and 0.01 M / L nitric acid, and the pH and temperature were limited to 4.0-8.0 and 288K-308K, respectively. The centrifuge tube was placed in a constant shaking box at 175 rpm for 0-12 hours. To ensure the effectiveness of the experiment, three sets of parallel samples were set up.

[0033] After adsorption, the solid and liquid phases were separated by filtration, and then part of the solution was taken through a UV-visible spectrophotometer and ICP was used to measure the ion concentration in the solution. The removal rate R (%) and adsorption capacity q were calculated using equations (1) and (2) respectively. e (mg / g).

[0034]

[0035] Where C0 (mg / L) and Ce (mg / L) are the concentrations of U(VI) in the solution before and after the reaction, respectively. V(L) is the volume of the solution, and m(mg) is the dry weight of Cu-MOF / CSTA. e (mg / g) is the adsorption capacity of Cu-MOF / CSTA for U(VI) at adsorption equilibrium.

[0036] Selective adsorption experiment:

[0037] A multi-component mixed metal ion solution of U, Zn, Cu, Al, Ca, and Mg was prepared, wherein the U(VI) ion concentration was 14.82 mg / L, the Al ion concentration was 5.7 mg / L, and the remaining metal ion concentrations were all 10 mg / L. The solution pH was adjusted to 5. The experimental process was the same as above, and the concentrations of metal ions in the solution before and after adsorption were determined by ICP-OES.

[0038] Real wastewater:

[0039]

[0040] Equation (3) was used to calculate the solid-liquid distribution coefficient k in the selective adsorption experiment d (mL / g).

[0041] Test results:

[0042] 1. Influence of initial pH and adsorbent dosage.

[0043] The initial pH value of the uranium solution is one of the important factors affecting adsorption. The pH value will affect the charge on the surface of the adsorbent and the type of uranyl ions in the solution. Figure 1 (a) shows the influence of the solution pH in the range of 4.0 - 8.0 on the adsorption of uranium by Cu-MOF@CSTA (initial uranium concentration is 10 mg / L). As the pH value of the uranium solution increases, the adsorption capacity first increases slightly and then decreases. When the pH value of the solution is 5.0, the adsorption amount reaches the maximum. The ζ potential of Cu-MOF@CSTA decreases with the increase of the pH value of the uranium solution. Near pH = 5.4, its Zeta potential is 0, which means that the pH of 5.4 is the isoelectric point of Cu-MOF@CSTA. According to the reports in the existing technology, UO2 2+ 、UO2OH + 、UO2(OH) + and (UO2)3(OH)5 + are the dominant species in the U(VI) solution at low pH values. In a strongly acidic environment, there are a large number of H + , and these H + will compete with UO2 2+ for coordination with the adsorbent, resulting in a decrease in the adsorption capacity. When the pH of the solution changes from 4 to 5, at this time pH < pHzpc, the H + existing in the acidic environment will decrease, which is beneficial to enhancing the coordination ability between UO2 2+ and Cu-MOF@CSTA, resulting in an increase in the adsorption capacity. As the pH value of the solution increases, the functional groups on the surface of Cu-MOF@CSTA begin to deprotonate and carry a negative charge. U(VI) mainly exists in the form of positively charged uranium hydrolysis products UO2 2 + 、UO2(OH) + at this time. When the pH of the solution changes from 5 to 6, the ζ potential changes from positive to negative. When the pH is greater than 6, the surface of Cu-MOF@CSTA is negatively charged, and the negatively charged (UO2(OH)3, UO2(OH)4 2- 、UO2(CO3)2 2- and UO2(CO3)34- ) also dominates the uranium solution, so there is a strong electrostatic repulsion between Cu-MOF@CSTA and U(VI), which leads to a decrease in its adsorption capacity. Experiments show that even under acidic conditions of pH 4, the adsorption rate remains above 96%, laying a good foundation for the application of treating real wastewater. Under the same environment, the dosage of the adsorbent was adjusted from 3mg to 15mg, and the relationship between the adsorption performance of the adsorbent (Cu-MOF@CSTA) for uranium and the dosage was analyzed, such as Figure 1 (b) shows how the adsorption efficiency and adsorption capacity of uranium change with the amount of adsorbent. When the adsorbent dosage is 3 mg, the adsorption rate is 81.84%. When the adsorbent dosage increases to 10 mg, the adsorption rate reaches 98.51%, and the adsorption capacity also reaches the maximum value at this time. This is because with the increase of adsorbent dosage, the effective active sites on the sample surface increase and the adsorption efficiency improves. In addition, further increasing the adsorbent dosage to 15 mg does not lead to an increase in the adsorption rate, but rather a decrease. This is because when the dosage of the absorbent is excessive, the adsorbent aggregates and the unbound active sites overlap, resulting in a reduction in the effective surface area required for adsorption. However, under the same conditions, when the dosage of Cu-MOF is 10 mg, the adsorption rate is 91.06%, which shows that the introduction of CS and TA effectively improves its adsorption performance.

[0044] 2. Effect of contact time and adsorption kinetics.

[0045] The adsorption kinetics revealed the adsorption process of uranium ions and determined the effect of the contact time between the solid adsorbent and the solution interface on uranium adsorption. The pseudo-first-order kinetic model and pseudo-second-order kinetic model were studied to evaluate the kinetic adsorption mechanism of Cu-MOF@CSTA for U(VI). Figure 2 The study investigated the adsorption of 10 mg of Cu-MOF@CSTA into 90.0 mL of uranium solution at 298 K, with a solution pH of 5 and a uranium concentration of 11.2 mg / L. Figure 2As shown, in general, the removal of U(VI) by Cu-MOF@CSTA is very rapid in the initial stage, and then gradually becomes slow. Within the first 30 minutes, the removal rate of U(VI) by Cu-MOF@CSTA has exceeded 94%, and equilibrium is reached in about 120 minutes. In the initial stage of adsorption, due to the presence of more active sites on the surface of Cu-MOF@CSTA, U(VI) and its compounds are more likely to occupy a large number of active sites, and the adsorption amount of U(VI) by Cu-MOF@CSTA increases rapidly. However, as the adsorption process proceeds, the number of adsorbents remains unchanged, the free adsorption sites gradually decrease, the probability of U(VI) and its compounds colliding with the free adsorption sites decreases, the adsorption driving force decreases, and the adsorption process gradually stabilizes. Table 1 lists the relevant kinetic parameters of the adsorption of U(VI) by Cu-MOF@CSTA under different kinetic models. By comparing the fitting coefficients R of the quasi-first-order kinetic model and the quasi-second-order kinetic model 2 (R1 2 =0.99010, R2 2 =0.99771), the results show that the adsorption of U(VI) by Cu-MOF@CSTA is more consistent with the pseudo-second-order kinetic model, indicating that the adsorption of U(VI) by Cu-MOF@CSTA is chemical adsorption.

[0046] Table 1Adsorption kinetic parameters of the U(VI)adsorption by theCu-MOF@CSTA.

[0047]

[0048] 3. Adsorption isotherm and adsorption thermodynamics.

[0049] The adsorption isotherm model comprehensively considers the equilibrium data and adsorption properties of the adsorbent and adsorbate. It depends on various physical properties of the adsorbed substance, adsorbate, adsorbent and solution, including pH, ionic strength and temperature. Langmuir and Freundlic are often used to simulate the adsorption behavior of U(VI) on MOF. As can be seen from Table 2, the Langmuir correlation coefficients R of Cu-MOF and Cu-MOF@CSTA are 2 Freundlich correlation coefficient R 2 The results show that the capture process of Cu-MOF and Cu-MOF@CSTA for U(VI) is mainly monolayer chemical adsorption. Adsorption experiments were carried out with different uranium concentrations (5mg / L-600mg / L) to analyze the effect of temperature on the adsorption of uranium concentration. The temperature was kept at 288.15K, 298.15K and 308.15K. Figure 3(a), (b) and (c). As the temperature increases from 288.15K to 308.15K, the amount of uranium adsorbed by Cu-MOF increases, indicating that the increase in temperature enhances the adsorption of uranium by Cu-MOF, confirming that the adsorption of uranium by Cu-MOF is an endothermic process. As the temperature increases, the amount of uranium adsorbed by Cu-MOF@CSTA decreases, which also indicates that with the introduction of CS and TA, the adsorption of Cu-MOF@CSTA becomes an exothermic process. In addition, compared with Cu-MOF, the adsorption capacity of Cu-MOF@CSTA has been greatly improved. At 298.15K, the maximum theoretical adsorption capacity of Cu-MOF@CSTA is 727.151 mg / g higher than that of Cu-MOF, and at 308.15K, the maximum theoretical adsorption capacity of Cu-MOF@CSTA is 186.383 mg / g higher than that of Cu-MOF. The results show that with the introduction of CS and TA, Cu-MOF was solidified, so that the maximum theoretical adsorption capacity of Cu-MOF@CSTA for uranium at a temperature of 288.15K reached 2507.732 mg / g. At this temperature, the maximum theoretical adsorption capacity of Cu-MOF@CSTA was 2.88 times higher than that of Cu-MOF, which is 1632.651 mg / g higher. This further shows that it has great potential in the adsorption of uranium-containing wastewater.

[0050] Table 2Thermodynamic parameters of the Langmuir and Freundlich models atvarious temperatures.

[0051]

[0052] 4. The influence of competing ions in selective adsorption.

[0053] There are a large number of competitive ions in radioactive wastewater, so the highly selective adsorption of uranium is an important parameter for evaluating adsorbents. In order to evaluate the adsorption selectivity of Cu-MOF@CSTA for acidic wastewater, an experimental simulation of uranium wastewater was carried out based on the competitive ions present in a real wastewater. Different metal ions including U(VI), Zn(Ⅱ), Cu(Ⅱ), Al(Ⅲ), Ca(Ⅱ), and Mg(Ⅱ) were introduced to form a six-element mixed metal ion solution. 10 mg of adsorbent was used to adsorb the metal ion solution with a pH of 5, the adsorption temperature was 298K, and the adsorption time was 12 h. Cu-MOF@CSTA has a higher adsorption capacity for U(VI), up to 116.41 mg / g, which is much higher than other metal cations. The solid-liquid partition coefficient K d Indicates that the result is Figure 4As shown in the figure, even in the presence of various metal cations, Cu-MOF@CSTA exhibits excellent U(VI) removal effect, indicating that it has a strong affinity for U(VI). d The value is 61754mL / g, and the K of U(VI) d The value is only slightly higher than that of Al(Ⅲ) d The value is 1.512 times higher. The selective adsorption characteristics of Al(Ⅲ) can be explained by the inherent characteristic of the first hydrolysis constant (-logβ1). The smaller the -logβ1, the easier it is for the metal ions to hydrolyze. In addition, the affinity of the hydrolyzed metal ions to the solid adsorbent is higher than that of the unhydrolyzed ions, indicating that the presence of Al(Ⅲ) has a certain competitiveness in the adsorption of U(VI), which reduces the adsorption capacity of Cu-MOF@CSTA for U(VI) to a certain extent. It can be seen from the figure that the K of Mg(Ⅱ) d The value is only 2.545mL / g. This is because when pH = 5, the surface charge of Cu-MOF@CSTA is about 6.05mV, so there is a strong Coulomb repulsion between the surface of Cu-MOF@CSTA and the alkali metal Ca(Ⅱ), which leads to a very low adsorption capacity of Cu-MOF@CSTA for Ca(Ⅱ). Therefore, it can be seen that under certain conditions, Cu-MOF@CSTA has broad application prospects in adsorbing uranium under acidic conditions.

[0054] 5. Adsorption of uranium in real wastewater by Cu-MOF@CSTA.

[0055] In view of the low concentration of uranium (VI) in real nuclear wastewater, the adsorption performance of Cu-MOF@CSTA on uranium was further studied, and adsorption experiments were carried out on uranium-containing wastewater (pore water and seepage water) from a uranium mine. The pH value of the pore water is 7.6, and the uranium concentration is 860.68μg / L. The pH value of the seepage water is 7.2, and the uranium concentration is 497.68μg / L. At 298K, 10mgCu-MOF@CSTA was used to conduct the experiment on the pore water and seepage water. After 12h of adsorption, the uranium concentrations in the pore water and seepage water dropped to 0, and the uranium removal rate was as high as 100%. Although there are many interfering co-existing ions in the wastewater, especially SO4 2- 、CO3 2- , Cl - 、C2O4 2- 、NO3 - and NH4 + However, Cu-MOF@CSTA still maintains a strong anti-interference ability, which further illustrates that Cu-MOF@CSTA has practical application prospects in treating various nuclear wastewaters.

[0056] Characterization

[0057] 1. BET analysis.

[0058] The Brunauer-Emmett-Teller (BET) method has been widely used to characterize the surface area of ​​porous materials by semi-empirical fitting of gas adsorption isotherms. Figure 5 As shown in Table 3. The experimental results show that the specific surface area of ​​Cu-BTC is 1013.7922m 2 / g, the average pore size is 1.8405nm. The specific surface area of ​​Cu-BTC is 1013.7922m 2 / g, with an average pore size of 1.8405nm, and a microporous structure. In contrast, the specific surface area of ​​Cu-BTC-Hc (i.e., Cu-MOF) is 324.114m higher than that of Cu-BTC. 2 / g, the average pore size of Cu-BTC-Hc is 0.242nm lower than that of Cu-BTC, indicating that the introduction of Hc (i.e., 4-hydroxy-2-mercapto-5-pyrimidinecarboxylic acid) improves the specific surface area, adsorption efficiency and adsorption capacity of Cu-BTC. The N2 curves of Cu-BTC-Hc and Cu-BTC conform to the reversible type I isotherm. The adsorption amount of type I isotherm increases rapidly at a lower relative pressure, and the adsorption appears saturated after reaching a certain relative pressure, which is similar to the Langmuir adsorption isotherm. The type I isotherm reflects the micropore filling phenomenon on Cu-BTC-Hc, and the saturated adsorption value is equal to the filling volume of the micropores. In addition, Cu-BTC and Cu-BTC-Hc have obvious H4 hysteresis loops, indicating that Cu-BTC and Cu-BTC-Hc have different types of pore structures (micropores and mesopores). This is also basically consistent with the previously reported synthesis of Cu-BTC. The specific surface area of ​​Cu-MOF@CSTA is 29.1575m 2 / g, with an average pore size of 25.3797nm, and a mesoporous structure. Compared with Cu-BTC-Hc, the specific surface area of ​​Cu-MOF@CSTA is reduced, which is also attributed to the stacking of surface molecules and partial blockage of pores caused by the curing of Cu-MOF-Hc with CS and TA, but CS and TA introduced a large amount of UO2 2+ Active functional groups with strong affinity improve the adsorption capacity and selective adsorption of uranium by Cu-MOF@CSTA. In addition, the specific surface area of ​​the modified MOF is inevitably reduced, which is consistent with previously reported literature.

[0059] Table 3BET parameters of Cu-BTC, CU-MOF, and CU-MOF@CSTA.

[0060]

[0061] 2. SEM-EDS analysis.

[0062] In order to observe the effect of the introduced new monomer Hc on the morphology of the prepared Cu-MOF material, as well as the changes in its morphology after the introduction of CS and TA, SEM characterization of Cu-BTC, Cu-BTC-Hc and Cu-MOF@CSTA was performed, respectively. Figure 7 As shown in the figure, Cu-BTC exhibits a complete octahedral structure, which is observed to be a crystal with sharp edges, which is consistent with the literature previously reported on the Cu-BTC metal organic framework. After the introduction of the new monomer Hc, the microstructure of Cu-BTC-Th changed slightly, and a regular, smooth and transparent crystal protruded from its surface, which also indicated the successful introduction of the ligand Hc. The SEM image of Cu-MOF@CSTA showed that there were a large number of interconnected pores distributed on its surface, showing a network structure, and also providing an effective channel for uranyl ions. Figure 7 As shown in (b), after the adsorption reaction, these holes on the surface are filled and slightly protruded. EDS was then used to analyze the changes in the element content before and after the adsorption of Cu-MOF@CSTA. Figure 6 As shown, in addition to the C, O, N and S elements present in the material, 9.85 wt% U(VI) was detected after adsorption, which further indicates that U(VI) was adsorbed by Cu-MOF@CSTA.

[0063] 3. FTIR analysis.

[0064] In order to confirm whether the new Hc ligand was successfully introduced in the process of preparing Cu-MOF and the changes in the functional groups after cross-linking CS and TA, infrared characterization was performed. The FTIR spectra of Cu-BTC, Cu-BTC-HC (Cu-MOF), Cu-MOF@CSTA and Cu-MOF@CSTA-U are shown in Figure 2. Figure 8 As shown. The FTIR spectrum of Cu-MOF is at 1580 cm -1 The peak at 1730 cm is attributed to the stretching vibration of the C=C bond of the benzene ring skeleton in Cu-BTC. -1 The vibration peak at 1566 cm is attributed to the -COOH stretching vibration of Cu-BTC. -1 and 1280cm -1 There are new vibration peaks at 3458cm, which are attributed to C=N stretching vibration and C=S stretching vibration. This can be understood as the nitrogen-containing functional group and the sulfur-containing functional group are successfully connected to the benzene ring skeleton after the introduction of Hc. The FTIR spectrum of Cu-MOF@CSTA is at 3458cm -1The vibration peak at 3458 cm is attributed to the stretching vibration of OH. Compared with the FTIR spectrum of Cu-MOF, the FTIR spectrum of Cu-MOF@CSTA has a peak at 3458 cm -1 The vibration peak at 1443 cm appears broader, which can also be explained by the group interaction between Cu-MOF and the surface of CSTA. -1 and 1353cm -1 The peak at 1610cm is attributed to the symmetric stretching vibration of O=CO. -1 The peaks near 1717cm are related to the asymmetric stretching vibration of O=CO. -1 The bands at 757 cm -1 The peak at 894 cm is attributed to the out-of-plane bending of Cu-MOF@CSTA. Cu-MOF@CSTA-U shows a peak at 894 cm -1 The new absorption peak at can be attributed to the stretching vibration of the O=U=O group. This also shows that Cu-MOF@CSTA successfully adsorbed uranium. From the above analysis, it can be seen that the main functional groups of Cu-MOF@CSTA in the process of uranium adsorption are -NH2 and -OH groups, as well as a small amount of nitrogen-containing and nitrogen-containing functional groups. This is also consistent with the results of XPS analysis.

[0065] 4. Raman analysis.

[0066] Raman and infrared spectroscopy data are important tools for studying the coordination chemistry of solid-state U(VI). Fig. 9 The Raman spectra of Cu-MOF@CSTA before and after adsorption are compared. -1 This band, with the highest point at 445cm -1 It is a fluorite structure UO close to the stoichiometric ratio 2+X The typical features of are closest, which also corresponds to the triply degenerate orbital T 2g Raman active vibration. In addition, this is also related to the stretching mode of UO, which is also one of the typical characteristics of stoichiometric UO2. -1 The band present in the range is 736.14 cm -1 This can be attributed to the stretching and bending vibrations of carbonates. The successful reduction of U(VI) from solution and its adsorption onto the formed UO2 were further demonstrated by analyzing Raman spectra.

[0067] 5. XPS analysis.

[0068] Fig. 9The XPS spectra of Cu-MOF@CSTA before and after the adsorption of U(VI) are shown. By comparing the chemical analysis and XPS results of Cu-MOF@CSTA and Cu-MOF@CSTA-U, the adsorption mechanism of Cu-MOF@CSTA on uranyl ions is revealed. C1s, N1s, O1s, Cu2p and S2p are shown in the spectrum. In addition, the U4f peak also appears in the XPS spectrum of Cu-MOF@CSTA-U. The U4f spectrum includes the U4f7 / 2 peak at 382.38eV and the U4f5 / 2 peak at 393.18eV. The appearance of the U4f peak indicates that Cu-MOF@CSTA has successfully adsorbed uranium. This is also consistent with the results of SEM-EDS analysis.

[0069] The N1s spectrum of Cu-MOF@CSTA can be divided into two peaks, centered at 400.19 eV and 402.33 eV, which are attributed to NC=O and -NH3, respectively. + peak. This also reveals the successful introduction of Hc and the cross-linking effect of tannic acid on chitosan. After adsorbing uranium, the position and intensity of the characteristic peaks of the Cu-MOF@CSTA-U spectrum changed significantly, because -NH3 + After protonation, it is converted into free -NH2. In addition, the peaks of Cu-MOF@CSTA-U change to 400.14eV and 402.19eV, respectively, which may be due to the UO 2+ A chelate is formed and electrons are shared with the nitrogen atom, resulting in a small decrease in the electron density on the nitrogen atom.

[0070] The C1s spectrum observation revealed that the peaks of 284.80 eV (CC), 286.01 eV (COC, C=S, C-OH) and 288.79 eV (OC=O, OCO, -CONH) shifted to 286.59 and 288.72 eV after the adsorption of U(VI), indicating that a small amount of C=S and -CONH participated in the reaction, and the dominant functional group in the adsorption process was C-OH. In the O1s spectrum, it can be observed that the peak at 532.92 eV belongs to the O element and -OH in the -COO···Cu family. After the adsorption of U(VI), the peak moved to a lower 532.90 eV, and its peak area also decreased. It may be that a small part of Cu(II) and U(VI) underwent ion exchange reaction during the adsorption process. This result is consistent with the EDS result.

[0071] In the Cu2p spectrum, Cu2p was observed 3 / 2 (934.62eV), Satellite (943.51eV) and Cu2p 1 / 2(954.28eV) shifted to the low binding energies of 934.47eV, 942.44eV and 954.15eV, respectively. The Cu 2+ It has a peak with relatively low binding energy, which also indicates that Cu(II) exists in a coordinated form.

[0072] From the S2p spectrum, we can see that S2p 3 / 2 The corresponding peak value is 164.38eV and is related to C=S. It shifts to 165.39eV after the adsorption of U(VI). The reason may be that a small amount of C=S is oxidized after reacting with U(VI) and a complex reaction occurs. The determination results of C1s, N1s, O1s, Cu2p and S2p show that after the introduction of Hc and CSTA, the adsorption process of Cu-BTC includes the synergistic effect of amino and hydroxyl groups, the complexation of sulfur-containing functional groups with U(VI) and a small amount of Cu 2+ The process of ion exchange between U(VI) and ion exchange between U(VI).

[0073] Therefore, the adsorption mechanism of uranium by Cu-MOF@CSTA is as follows: after Hc is introduced on Cu-BTC, the nitrogen-containing functional groups and -C=S functional groups show good coordination ability with U(VI) ions. Through ion exchange with Cu(II) ions, U(VI) ions enter the adsorbent and coordinate with carboxyl groups, which significantly improves the adsorption performance of Cu-MOF (Cu-BTC-Hc) for U(VI) ions. Subsequently, TA cross-linked CS composite Cu-MOF, which not only solidified Cu-MOF, but also enhanced its stability, and also introduced a large amount of UO2 2+ The amino, hydroxyl and other functional groups with strong affinity also make the final adsorbent material Cu-MOF@CSTA show such excellent performance in adsorbing uranium.

[0074] The Cu-MOF / chitosan / tannic acid composite adsorbent prepared by the present invention can be used to adsorb uranium in uranium-containing wastewater. Kinetic and thermodynamic experiments show that the theoretical maximum adsorption capacity of Cu-MOF@CSTA for U(VI) is 2507.73 mg / g (288K, pH=5.0), which is a spontaneous exothermic reaction. The removal rate of uranium in uranium-containing wastewater (pore water and seepage water) from uranium mines reaches 100%. Mechanism analysis shows that the synergy of hydroxyl, amino and sulfur-containing functional groups on the surface of Cu-MOF@CSTA, as well as Cu 2+ With UO2 2+ The ion exchange process jointly promoted the adsorption of uranium by Cu-MOF@CSTA. The competitive adsorption experiment showed that Cu-MOF@CSTA had good uranium adsorption selectivity. Tannic acid cross-linked chitosan as a flexible carrier and solidified Cu-MOF, making it have great potential in the adsorption of uranium-containing wastewater.

[0075] In order to make it easier for ordinary technicians in the field to understand the improvements of the present invention over the prior art, some drawings and descriptions of the present invention have been simplified, and the above-mentioned embodiments are preferred implementation schemes of the present invention. In addition, the present invention can also be implemented in other ways. Any obvious replacement without departing from the concept of the present technical solution is within the protection scope of the present invention.

Claims

1. A method for preparing a Cu-MOF / chitosan / tannic acid composite adsorbent, characterized in that: A certain amount of deionized water is added to an appropriate amount of tannic acid, stirred until completely dissolved, and then an appropriate amount of chitosan, Cu-MOF and glacial acetic acid are added, stirring is continued, and then an appropriate amount of glutaraldehyde solution is added. After shaking and freeze-drying, a Cu-MOF / chitosan / tannic acid composite adsorbent is obtained.

2. The method for preparing the Cu-MOF / chitosan / tannic acid composite adsorbent according to claim 1, characterized in that: The preparation steps of the Cu-MOF include: taking an appropriate amount of Cu(NO)2·3H2O and dissolving it in ultrapure water, ultrasonically dissolving an appropriate amount of 4-hydroxy-2-mercapto-5-pyrimidinecarboxylic acid and H3BTC, and adding them to the dissolved Cu(NO)2·3H2O solution, stirring at room temperature, reacting at a certain temperature, and then performing solid-liquid centrifugation, and then washing with anhydrous ethanol for multiple times, placing the washed product in anhydrous ethanol for activation, and drying the activated product to obtain the Cu-MOF.

3. The method for preparing the Cu-MOF / chitosan / tannic acid composite adsorbent according to claim 1, characterized in that: The concentration of the glutaraldehyde solution is 0.1%.

4. The method for preparing the Cu-MOF / chitosan / tannic acid composite adsorbent according to claim 1, characterized in that: The shaking method is to shake at a frequency of 150 times per minute for 24 hours in an environment of 45°C.

5. A Cu-MOF / chitosan / tannic acid composite adsorbent, characterized in that: The preparation method is described in any one of claims 1 to 4.

6. The use of the Cu-MOF / chitosan / tannic acid composite adsorbent according to claim 5, characterized in that: Used to adsorb uranium metal in uranium-containing wastewater.

Citation Information

Cited By

  • Chitosan-citric acid cross-linked bamboo charcoal-based composite adsorbent as well as preparation method and application thereof

    CN121550967A